Growth and productivity of trees and intercrops under agroforestry system in red and lateritic zone of West Bengal - Banerjee, Hirak; Dhara, Pratap Kumar; Maiti, Sunirmal; Pal, Sukanta (Indian Journal of Agroforestry, 2020)
To evaluate the growth and productivity of Azadirachta indica, Eucalyptus tereticornis, Acacia plectocarpa and Shorea robusta planted under Agri-silviculture system with 4 different intercrops [groundnut (Arachis hypogaea), rice (Oryza sativa), cowpea (Vigna unguiculata) and blackgram (Vigna mungo)], a field experiment was conducted on lateritic soil of West Bengal. Intercrops were grown during rainy season (kharif) only i.e. under rainfed condition. The result revealed that tree height, diameter at breast height (dbh) and volume of wood of trees were increased gradually with the increasing age of the trees but the rate of increment of heights and dbh was shown in a phasic manner due to change of climate throughout the year. Growth rates of Azadirachta sp. and Shorea sp. were a bit slower than Eucalyptus sp. And Acacia sp. Productivity of intercrops grown under Azadirachta tree cover was slightly higher as compared to other three trees. Among different intercrops, blackgram gave maximum return irrespective of different agri-silvicultural systems. Net return and B : C ratio was recorded maximum under Azadirachta based agri-silviculture system. It was closely followed by that of Eucalyptus sp. The Soil moisture content was reduced in all the depths of soil where Eucalyptus tree was grown but it was increased under Azadirachta tree cover.